Women Who Sexually Abuse Children – Results From an Anonymous Online Survey Among a Non-Forensic Female Sample With Sexual Interest in Children - Tozdan, Safiye (Sexual offending, 2025)
Knowledge is still rare regarding women who commit child sexual abuse (CSA), especially those who have a sexual interest in children. The present study aimed at assessing characteristics of CSA committed by women. We investigated self-report data from 23 German women from the general population who reported a sexual interest in children and previous acts of CSA. Results showed that participants were mostly well-educated with almost no reported childhood maltreatment. At first offence, participants were 25.22 years and children (65.2% female) were 5.30 years on average. 95.5% of participants were known or related to the child and all of them conducted at least one contact sexual offense. 87% stated they conducted the sexual acts for “sexual satisfaction”; 34.8% out of “love”; 30.4% for “physical closeness”; and 34.8% for “emotional closeness”. The results indicate that participants conduct the offence voluntarily and were not coerced by anyone else to engage in CSA. Our results might indicate that women who commit CSA and have a sexual interest in children may constitute a specific subtype that differs in several ways from forensic samples of women committing CSA examined in the past.